The White Swans of the Russian Wedding Song - Czerwiński, Piotr (W kręgu zagadnień języka, literatury i kultury: Księga jubileuszowa dedykowana Profesorowi Jarosławowi Wierzbińskiemu, 2022)
The two selected sources (Siberian and north Russian wedding ceremonies) give semantic projections of “the white swan/pen” towards a fiancée. They are described as “a personal female, maternal, nursing and ancestral” element and a personification of girl’s mommy, dear sister(s), female friends, female relatives and of course the girl’s beauty which she must leave. The bride-to-be / fiancée is called a cygnet or a white swan in the songs performed by her female friends as well as by the family of her future husband. Her own ancestral element from her point of view is regarded as “swans,” “flock of swans.” On the other hand, from the point of view of the bridegroom, this is called “geese,” “flock of geese,” “goose’s.” Finally, the fiancée must leave her flock of swans to join her husband’s flock of geese. The above observations and their results are related to the folk traditions – in fairy tales, proverbs, catchphrases, and riddles.